2022
DOI: 10.1007/s10071-022-01636-2
|View full text |Cite
|
Sign up to set email alerts
|

Bridging pure cognitive research and cognitive enrichment

Abstract: Cognitive enrichment is a growing subset of environmental enrichment for captive animals. However, it has been difficult for practitioners to design, implement, and evaluate relevant and appropriate cognitive challenges. Even though pure comparative cognition researchers focus on fundamental evolutionary questions, their knowledge and expertise can also shape the future of cognitive enrichment. This paper describes the motive, means, and opportunity to do so. Taxon-specific summaries of animal cognition (inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…Five out of six animals interacted consistently with the device across several months, in sessions of 3 h duration during which fluid and food were available ad libitum . This was presumably due to the sugary fluid reward delivered by the device in combination with the provision of an activity that provided a form of cognitive enrichment ( Murphy et al, 2003 ; Tarou and Bashaw, 2007 ; Clark, 2017 , 2022 ; Calapai et al, 2022 ). On the other hand, we found that engagement strongly depended on short-term performance levels as the likelihood of initiating a trial decreased with an increase in difficulty and throughout the training section in which the task gradually moved from visuo-acoustic to acoustic only.…”
Section: Discussionmentioning
confidence: 99%
“…Five out of six animals interacted consistently with the device across several months, in sessions of 3 h duration during which fluid and food were available ad libitum . This was presumably due to the sugary fluid reward delivered by the device in combination with the provision of an activity that provided a form of cognitive enrichment ( Murphy et al, 2003 ; Tarou and Bashaw, 2007 ; Clark, 2017 , 2022 ; Calapai et al, 2022 ). On the other hand, we found that engagement strongly depended on short-term performance levels as the likelihood of initiating a trial decreased with an increase in difficulty and throughout the training section in which the task gradually moved from visuo-acoustic to acoustic only.…”
Section: Discussionmentioning
confidence: 99%
“…Having established that most animals exhibited a task preference with the multiplechoice interface, we evaluated whether such engagement is purposeful or casual [18,56], and by extension, whether animals engage with the challenge using their own competence and potentially develop mastery. We found that the hit rate in the static task across all animals was already above chance at the smallest stimulus size we tested (namely 5 degrees of visual angle) and the hit rate increased with increasing stimulus size above chance level (Figure 4a).…”
Section: Task Proficiencymentioning
confidence: 99%
“…The animals consistently engaged with the tasks, exhibited individual task preferences, and demonstrated proficiency in performing the selected tasks. Our approach has the potential to improve the psychological well-being of captive animals while providing researchers with a reliable and scalable method for conducting scientific research on animal cognition and welfare simultaneously [56,67].…”
Section: Practical Implications and Future Directionsmentioning
confidence: 99%